The Influence of Milling Parameters on Cutting Forces in High-Speed Milling of Polymer Materials - Uysal, Alper; Dzhemilov, Eshreb; Dzhemalyadinov, Ruslan (SPRINGER INTERNATIONAL PUBLISHING AG, 2020)
This article presents the results of experimental studies during highspeed end milling of pure and carbon black reinforced polyamide materials depending on the cutting conditions used. The physicomechanical properties of such materials largely depend on the technological requirements of their manufacture. The high elastic properties of the polymer materials and their composites contribute to an increase in the contact area of the tool with the workpiece, especially on the back surface, thereby leading to an increase in the cutting forces. The result of this phenomenon causes a decrease in the critical wear threshold of the tool compared to metal processing. Based on this experimental study, it was found that milling of pure polyamide couldn't be performed at the cutting speeds beyond 500 m/min due to the occurring high temperature at the contact area. The cutting forces for both polymer materials increased as the feed and cutting speed increased. Furthermore, when comparing carbon black reinforced and pure polyamide materials, it was observed that more cutting force is needed for milling of pure polyamide material.
Keywords: High-speed milling; Carbon black reinforced polyamide; Cutting forces; SURFACE-ROUGHNESS; PREDICTION; Engineering